2023
DOI: 10.1038/s41598-023-27844-5
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of spermine coated iron nanoparticles and its effect on biochemical properties of Rosmarinus officinalis

Abstract: In this study, aqueous spinach extract was used for the green synthesis of iron nanoparticles. The surface of iron oxide nanoparticles was coated with spermine. The physicochemical properties of nanoparticles were investigated using UV-Vis, TGA, FTIR, VSM, TEM, and DLS. The results showed that the nanoparticles had a spherical structure. The surface charge of the Fe3O4-NPs increased from −3.2 to 18.42 (mV) after Fe3O4 coating by spermine. In order to investigate the effect of nanoparticles on physicochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…On the other hand, under stressful conditions, it has been shown that applying Fe 3 O 4 -NPs and single-branched and multibranched polyamines promoted proline accumulation. According to the study, Fe 3 O 4 -NPs and polyamines increase proline accumulation, free amino acid content, antioxidant enzyme activity, nutritional content, and plant tolerance to environmental stressors …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, under stressful conditions, it has been shown that applying Fe 3 O 4 -NPs and single-branched and multibranched polyamines promoted proline accumulation. According to the study, Fe 3 O 4 -NPs and polyamines increase proline accumulation, free amino acid content, antioxidant enzyme activity, nutritional content, and plant tolerance to environmental stressors …”
Section: Results and Discussionmentioning
confidence: 99%
“…Finally, using a freeze-dryer, the product was collected and dried (Christ Alpha 1–4 LD plus, Germany) (Figure ). , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of microorganisms or plant extracts to synthesize nanoparticles allows for obtaining nanoparticles with high biocompatibility. Recent research showed that nanoparticles synthesized by such green synthesis methods have surfaces coated with proteins, fibers, and carbohydrates that provide them greater biocompatibility than those of the same size and shape but synthesized using chemical methods [ 38 , 39 ].…”
Section: Nanoparticle Toxicitymentioning
confidence: 99%